Y2BaCuO5 Particle Size Control via Ultrasonication and its Effect on Bulk YBa2Cu3Oy Superconductor. Issue 1 (February 2020) - Pinmangkorn, S; Miryala, M; Arvapalli, S S; Murakami, M
Abstract: Recently, bulk LRBa2 Cu3 Oy (LRE: Y, Gd, Sm, NEG) superconducting materials became a popular choice for engineering applications such as high-field magnet systems for medical devices, rotating machine, magnetic bearings, etc. YBa2 Cu3 Oy (Y-123) is a trending high temperature superconducting material with a high critical temperature around 91 K. The superconducting performance of bulk YBa2 Cu3 Oy (Y-123) can be dramatically improved by controlling initially added Y2 BaCuO5 (Y-211) secondary phase particles and optimizing its processing conditions in the top seeded melt-growth (TSMG). In this work, we employed a low-cost ultrasonication technique to control size of initially added secondary phase Y-211 particles. The ultrasonication time is varied from 20 to 80 minutes along with a 20 minutes interval while maintaining constant power of 300 W and 20 kHz frequency. We had successfully prepared nanometre sized secondary phase Y-211 particles. Top seeded melt textured bulk Y-123 (20 mm diameter) were prepared with utilizing refined Y-211. The magnetization measurements exhibited a sharp superconducting transition temperature with Tc, onset around 91 K. Critical current density ( Jc ) and trapped field measured at 77 K exhibited higher value in bulk prepared with Y-211 secondary phase particles ultrasonicated for 80 minutes. The highest trapped field of 0.42 T at 77 K was recorded 0.3 mm above centre of the Y-123 bulk's surface. The self-field critical current density was around 47 kA/cm2 at 77 K (H// c -axis). The present results demonstrate that the performance of bulk Y-123 can be improved by controlling Y-211 secondary phase particle size via a low cost ultrasonication process.